Revisão do gênero Sternechus Schoenherr, 1826 (sensu Rosado-Neto, 1996)(Coleoptera, Curculionidae, Molytinae, Sternechini) - Sousa, Wesley Oliveira de (2004)
Orientador: Prof. Dr. Germano H. Rosado Neto